-6y=55-13

Simple and best practice solution for -6y=55-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y=55-13 equation:


-6y=55-13

We simplify the equation to the form, which is simple to understand
-6y=55-13

We move all terms containing y to the left and all other terms to the right.
-6y=+55-13

We simplify left and right side of the equation.
-6y=+42

We divide both sides of the equation by -6 to get y.
y=-7

See similar equations:

| 23d=621 | | 4x+7=55-2 | | (3x+6)+(2x-4)= | | m/7-5=60 | | 5.2y=4435.6 | | 16xy^4-32x^5y+20x^2y^2= | | 1*8=a | | (9x+45)*2=360 | | w-4+2w=28 | | 2(4c-1)-3=6c+9 | | 3.1e=37.2 | | -5x-11=3y+7 | | 49a^4b^2+25a^3b-17ab= | | -92=-4v+4(1-7v) | | 16y^3-32y^2-48y= | | -4(-3a-2)=13a+4 | | 6(x-4)=3x-12 | | 9x+45=360 | | 4x+5+3x=47 | | .5+5x=100 | | 7u=56 | | 125+45f=80 | | 5(5+25)= | | 3.7t=341.51 | | b(x-1)=d | | 6x+7-5x=16 | | 4-8x=-30 | | 325=(x+y)+75 | | 13=11+u | | -4x+6y=-6 | | -3x-2=-2 | | 76=4+4x |

Equations solver categories